Seasonal shifts in diurnal variations of pCO2 and O2 in the lower Ganges River. Issue 3 (1st April 2022) - Haque, Md. Morshedul; Begum, Most Shirina; Nayna, Omme K.; Tareq, Shafi M.; Park, Ji‐Hyung
Abstract: High‐frequency, paired measurements of the partial pressure of CO2 ( p CO2 ) and dissolved O2 were combined with dissolved organic matter (DOM) characterization to investigate diurnal (7:00–19:00) and seasonal variations in CO2 dynamics in the lower Ganges River. Diurnal variations in p CO2 shifted seasonally, concurring with changes in DOM optical properties, biodegradable DOM, and O2 departures from atmospheric equilibrium (ΔO2 ). Increased p CO2 and CO2 flux ( F CO2 ) in August–September corresponded to monsoonal floods carrying more terrestrial materials. Lower dry‐season p CO2 and F CO2 concurred with higher ΔO2, and exhibited strong relationships with DO and pH, indicating a dominant influence of phytoplankton production. Despite large variations in p CO2, the year‐long positive F CO2 implied that the lower Ganges acted as a CO2 source, reaching 122 mmol m −2  d −1 . Increasing hydrologic variability and pollution in the Ganges Basin can amplify p CO2 variations linked to seasonal shifts in terrestrial inputs and phytoplankton production.